Manajemen kepemimpinan kepala sekolah berbasis Asta Brata di SMK Negeri 1 Tembuku - I Gede Eka Pastika Eka; I Nyoman Subagia; Ida Ayu Adi Armini (UHN IGB Sugriwa Denpasar, 2023)
Abstract Currently, the government has budgeted funds for the implementation of the education sector in the amount of 20% of the APBN/APBD which aims to increase Indonesia's human resources. The goal of national education is to develop the potential of students to become human beings who believe in and fear God Almighty, have noble character, are healthy, knowledgeable, capable, creative, independent and become democratic and responsible citizens. The current phenomenon shows that the results of education nationally are still in an apprehensive condition. Therefore it is necessary to update school management materials through the teachings of Asta Brata in school management. This study focuses on three formulations of the problem, namely (1) What is the pattern of Asta Brata-based principal leadership management at Tembuku 1 State Vocational School?, (2) What factors support and hinder the Asta Brata-based principal leadership management process at State Vocational High School 1 Tembuku?, (3) What are the steps in improving Asta Brata-based principal leadership management at Tembuku 1 State Vocational School?. The problem is studied by using several theories, namely; Educational management theory, convergence theory, and structural functionalism theory. This research is qualitative using a naturalistic approach. Data collection was carried out by observation, interviews, literature studies, document studies. The results showed that the implementation of the teachings of Asta Brata in school management at SMK Negeri 1 Tembuku was very good and positive, as evidenced by the realization of a harmonious relationship between school members and the community through religious activities that give social religious meanings to the development of school management. Key words: Asta Brata Based and School Management